2006
DOI: 10.1021/ol0612307
|View full text |Cite
|
Sign up to set email alerts
|

Porphyrins Bearing Stable meso-Alkylidenyl Double Bonds. A New Family of Nonplanar Porphyrinoids

Abstract: [Structure: see text] Unique core-modified porphyrinoids, such as oxabenziporphyrins, oxapyriporphyrins, and thiapyriporphyrins, bearing exocyclic C-C double bonds at meso-positions, have been synthesized and characterized. The synthesis was accomplished by utilizing typical "3+1"-type condensation. Two different stable tautomeric forms were isolated, and the two tautomeric forms can be interconvertible upon treatment with base. In contrast, only the structure bearing an exocyclic double bond was isolated in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
18
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 19 publications
2
18
0
Order By: Relevance
“…The acid‐catalyzed condensation of pyrrole with 5 afforded desired building block 6 in 62 % yield. Many different conditions were tested in an effort to optimize this condensation, and it was found that the highest yield of 6 was obtained when TFA was used as a catalyst . Although these reactions afforded a single regioisomer, the 1 H NMR spectrum of 6 indicated the formation of diastereomers.…”
Section: Resultsmentioning
confidence: 99%
“…The acid‐catalyzed condensation of pyrrole with 5 afforded desired building block 6 in 62 % yield. Many different conditions were tested in an effort to optimize this condensation, and it was found that the highest yield of 6 was obtained when TFA was used as a catalyst . Although these reactions afforded a single regioisomer, the 1 H NMR spectrum of 6 indicated the formation of diastereomers.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless the spectroscopically documented merging of benzene with the macrocyclic conjugation is supported by the bond lengths observed for the ortho ‐benzene fragment (from 1.386(11) to 1.420(10) for 2 ‐H and from 1.368(4) to 1.424(4) Å for 6 ; see the Supporting Information), thus showing a significant difference when compared to the meta variant (1.378(2) to 1.399(2) Å) where isolation of the benzene ring from a macrocyclic conjugation has been documented 4b. 17 The data is similar to that of the para system (1.365(2) to 1.411(2) Å) which is shown to be part of the conjugated system 3…”
Section: Methodsmentioning
confidence: 99%
“…These observations were consistent The meso-alkylidenyl double bonds are of great importance for the stabilization of the nonaromatic macrocycle system. 75 Phenanthroline in the structurally flexible 106 provided two juxtaposed neutral nitrogen binding sites for smaller Mg 2+ ion. In 0.1 M HEPES buffer (DMSO/H 2 O = 7 : 3 v/v, pH 7.4), both the absorption and emission band of 106 redshifted from 496 to 575 nm and from 583 to 631 nm upon addition of Mg 2+ , respectively.…”
Section: Porphyrinoids Embedded With Type III Building Blocksmentioning
confidence: 99%